Demystifying Religious Tolerance Practices at an Indonesian Early Childhood Education Context: Responding to Diversity - Muallifatul Khorida Filasofa, Lilif; Prayogo, Agus; Khasanah, Felakhah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – Teaching religious tolerance should be conducted from early childhood, but studies and references on religious tolerance among young children are limited. This study explores how to implement religious tolerance in schools and how early Muslim children instill religious values in response to diversity. Design/methods/approach – This study was an exploratory case study deploying an ethnographic classroom approach conducted in a playgroup and kindergarten in Semarang city, Central Java, Indonesia. The participants consisted of the school principal, teachers, Play Group students, and Kindergarten children, while the empirical data of this research were gathered through observation and interview. Findings – The findings showed that religious tolerance at the early childhood education level was enacted by celebrating religious events and conducting school activities containing togetherness. Additionally, religious teachings that supported religious tolerance were inculcated during religious lessons and worship. Research implications/limitations – All study respondents were from Semarang City, Indonesia, which might limit the generalizability of the findings. Practical implications – This case study demonstrated how religious tolerance and religious values inculcation prepare children to encounter and respond to diversity in a real-life setting. Originality/value – This paper contributes to understanding the implementation of religious tolerance in schools and recommends teachers design lesson plans that include inculcating the values of religious tolerance. Paper type Case study